Community Empowerment Strategy Through Non-Formal Education in Increasing Participation in Tourism Village Management in Ogan Komering Ulu Regency - Zelpi Sapriana; Yudan Hermawan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to examine community empowerment strategies through non-formal education to increase community participation in the management of tourism villages in Kelumpang Village, Ogan Komering Ulu Regency. The researchers used a qualitative, descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation, involving the community, tourism managers, and related parties as informants. The results of the study indicate that community empowerment strategies are implemented through skills training, outreach, mentoring, the use of digital technology, and strengthening community institutions. These strategies are participatory, contextual, and sustainable, thus increasing community capacity in terms of knowledge, skills, and attitudes. Community participation has increased, as demonstrated by involvement in the planning, implementation, and evaluation stages of tourism village management, although not evenly distributed. Supporting factors include natural resource potential, economic opportunities, and community social support, while inhibiting factors include low awareness among some communities, limited human resource capacity, and suboptimal institutional arrangements. Thus, non-formal education plays a strategic role in encouraging increased community participation in the sustainable management of tourism villages.